ChemInform Abstract: Dynamic Heteroleptic Metal‐Phenanthroline Complexes: From Structure to Function. Issue 19 (13th May 2014) - Saha, Manik Lal; Neogi, Subhadip; Schmittel, Michael
Abstract Review: 115 refs.